PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWERPOINT UNTUK MENINGKATKAN PEMAHAMAN DAN MOTIVASI SISWA KELAS VIII SMP - LAIA, AGUSTINA MARNATA; ZEGA, NOVELINA ANDRIANI; GULO, HARDIKUPATU; TELAUMBANUA, DESMAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research aims to determine the feasibility, practicality and effectiveness of power point-based learning media and to determine the increase in student motivation in learning. This research uses the ADDIE development model design which consists of five stages, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation (evaluation). The product trial was carried out at SMP Negeri 1 Mazo in class VIII for the 2023/2024 academic year. Research results: (1) The percentage of presentation feasibility by the first material expert is 84,72%, the criteria are valid, by the second material expert the percentage is 81,94% the criteria are valid, by the linguist the percentage is 80,77% the criteria are valid, and by the design expert the percentage is 82,29%, the criteria are valid. (2) Students' responses to PowerPoint-based learning media products in individual tests obtained an average percentage of 72,22%, the criteria were practical, in small group trials the percentage was 79,67%, the criteria were practical, and in the field test the percentage was 88,53% criteria is very practical. (3) The effectiveness of students' understanding of learning through the development of PowerPoint-based learning media products obtained a percentage of students' learning completeness, namely 84,62% with very high criteria.. (4) Learning motivation of class VIII students at SMP Negeri 1 Mazo through the use of PowerPoint-based learning media products. The percentage of results from the initial stage learning motivation questionnaire is 64,15% the criteria are sufficient, and the results of the final stage learning motivation questionnaire are 87,69% the criteria are good. ABSTRAKPenelitian ini bertujuan untuk mengetahui kelayakan, kepraktisan, dan efektivitas media pembelajaran berbasis power point serta untuk mengetahui peningkatan motivasi peserta didik dalam belajar. Penelitian ini menggunakan desain model pengembangan ADDIE yang terdiri dari lima tahap antara lain yaitu: (1) Analisis (analyze), (2) Perancangan (design), (3) Pengembangan (development), (4) Implementasi (implementation), (5) Evaluasi (evaluation). Uji coba produk dilaksanakan di SMP Negeri 1 Mazo pada kelas VIII Tahun Pelajaran 2023/2024. Hasil penelitian: (1) Kelayakan penyajian oleh ahli materi pertama persentasenya yaitu 84,72% kriterianya valid, oleh ahli materi kedua persentasenya yaitu 81,94% kriterianya valid, oleh ahli bahasa persentasenya yaitu 80,77% kriterianya valid, dan oleh ahli desain persentasenya yaitu 82,29% kriterianya valid. (2) Respon peserta didik terhadap produk media pembelajaran berbasis power point pada uji perseorangan diperoleh rata-rata persentasenya yaitu 72,22% kriterianya praktis, pada uji coba kelompok kecil persentasenya yaitu 79,67% kriterianya praktis, dan pada uji lapangan persentasenya yaitu 88,53% kriterianya sangat praktis. (3) Efektivitas pemahaman belajar peserta didik melalui pengembangan produk media pembelajaran berbasis power point diperoleh persentase ketuntasan belajar peserta didik yaitu 84,62% dengan kriteria sangat tinggi. (4) Motivasi belajar peserta didik kelas VIII SMP Negeri 1 Mazo melalui penggunaan produk media pembelajaran berbasis power point persentase hasil angket motivasi belajar tahap awal yaitu 64,15% kriterianya cukup, dan hasil angket motivasi belajar tahap akhir yaitu 87,69% kriterianya baik.